Flotillins/cavatellins are differentially expressed in cells and tissues and form a hetero-oligomeric complex with caveolins in vivo. Characterization and epitope-mapping of a novel flotillin-1 monoclonal antibody probe. - Volonte, D.; Galbiati, F.; Li, S.; Nishiyama, K.; Okamoto, T.; Lisanti, M.P. (Journal of Biological Chemistry, 1999)
Caveolae are vesicular organelles that represent a subcompartment of the plasma membrane. Caveolins and flotillins are two families of mammalian caveolae-associated integral membrane proteins. However, it remains unknown whether flotillins interact with caveolin proteins to form a stable caveolar complex or if expression of flotillins can drive vesicle formation. Here, we examine the cell type and tissue-specific expression of the flotillin gene family. For this purpose, we generated a novel monoclonal antibody probe that recognizes only flotillin-1. A survey of cell and tissue types demonstrates that flotillins 1 and 2 have a complementary tissue distribution. At the cellular level, flotillin-2 was ubiquitously expressed, whereas flotillin-1 was most abundant in A498 kidney cells, muscle cell lines, and fibroblasts. Using three different models of cellular differentiation, we next examined the expression of flotillins 1 and 2. Taken together, our data suggest that the expression levels of flotillins 1 and 2 are independently regulated and does not strictly correlate with known expression patterns of caveolin family members. However, when caveolins and flotillins are co-expressed within the same cell, as in A498 cells, they form a stable hetero-oligomeric "caveolar complex." In support of these observations, we show that heterologous expression of murine flotillin-1 in Sf21 insect cells using baculovirus-based vectors is sufficient to drive the formation of caveolae-like vesicles. These results suggest that flotillins may participate functionally in the formation of caveolae or caveolae-like vesicles in vivo. Thus, flotillin-1 represents a new integral membrane protein marker for the slightly larger caveolae-related domains (50-200 nm) that are observed in cell types that fail to express caveolin-1. As a consequence of these findings, we propose the term "cavatellins" be used (instead of flotillins) to describe this gene family.